Cloud-based Business Applications Development Methodology - Benfenatki, Hind; Ferreira da Silva, C.; Benharkat, Aïcha-Nabila; Ghodous, P. (Proc. of the 23rd IEEE International Conference on Enabling Technologies: Infrastructure for Collaborative Enterprises (WETICE), 2014)
Nowadays, cloud applications are developed in Platforms as a Service and Infrastructures as a Service. Before the advent of Cloud computing, software engineering knew several approaches and methodologies for application development like: agiles methods and service oriented approaches. With cloud computing and the convergence toward ”Everything as a Service”, application development methods are moving to a new paradigm which abstracts the underlying architecture and infrastructure. We find in the literature, some work describing frameworks and architectures for cloud software development, but there is a lack of a methodology which covers the whole application development lifecycle. Furthermore, these work are mainly dedicated to developers. Our work fits into the perspective of defining a methodology for automatic cloud-based services-oriented business application development. The methodology we propose is designed for non-IT professional users. It avoids the huge technical background needed for cloud application development by automating the process of development; avoids PaaS dependency and advocates the implicit collaboration by reusing and composing services. We define a ”requirements vocabulary”, which is based on linked USDL principles and aims to describe the application requirements in a high level of abstraction of the development details.